Sistemas agroflorestais e seus efeitos sobre os atributos químicos em Argissolo Vermelho-Amarelo do Cerrado piauiense - Iwata, Bruna De F.; Leite, Luiz F. C.; Araújo, Ademir S. F.; Nunes, Luis A. P. L.; Gehring, Christoph; Campos, Liliane P. [UNESP] (Departamento de Engenharia Agrícola - UFCG, 2012)
This study aimed to quantify the effects of agroforestry systems (AFS), with different periods of adoption, and slash and burn agriculture (SB) on the chemical attributes of an Ultisol in the 'Cerrado' of Piaui State, Brazil. In two distinct climatic seasons (dry and rainy) four systems were studied: AFS with six (AFS6) and thirteen years (AFS13) of adoption, an area under SB and a native forest (NF), as a reference. In the AFS, in all depths, higher reduction in the Al3+ and H+ + Al3+ contents were observed as well as an increase of pH value and contents of nutrients (N, P, Ca, Mg and K) and organic carbon in soil. In the soil under SB, only in superficial layers, the ash deposited on the soil caused an increase in contents of nutrients, except for P, which was higher in all the depths. There was significant seasonal effect in the contents of nutrients, reducing in the rainy season. Agroforestry systems promoted increase in the nutrient contents of an Ultisol and can be considered useful to improve soil chemical quality in areas of 'Cerrado' of Piauí State, Brazil.

Objetivou-se, com este trabalho, quantificar os efeitos dos Sistemas Agroflorestais com diferentes tempos de adoção e a agricultura de corte e queima sobre os atributos químicos de um Argissolo Vermelho-Amarelo em áreas de cerrado do estado do Piauí. Em duas épocas climáticas foram estudados quatro sistemas: sistemas agroflorestais com seis e treze anos de adoção, agricultura de corte e queima e uma floresta nativa do cerrado. As amostras de solo foram coletadas em quatro profundidades para determinação dos atributos químicos. No solo sob os Sistemas Agroflorestais foram observados, em todas as camadas avaliadas, redução dos teores de Al3+ e H++Al3+ e aumento do pH, dos teores dos nutrientes e do carbono orgânico total em relação aos demais sistemas. No solo sob agricultura de corte e queima, verificou-se que apenas nas camadas superficiais a cinza depositada sobre o solo promoveu aumento dos nutrientes, exceto para o P, que foi maior em todas as camadas. Nos demais sistemas houve diminuição dos teores dos nutrientes no período chuvoso. Os sistemas agroflorestais promoveram aumento dos teores de nutrientes do solo e garantiram melhoria da qualidade química do solo em áreas de cerrado no estado do Piauí.
Agroforestry systems and its effects on chemical attributes of an Ultisol in the 'Cerrado' of Piaui state, Brazil
Keywords: soil conservation; soil quality; sustainable management; conservação do solo; qualidade do solo; manejo sustentável